Simbol pada Makam Syekh Bil Ma’ruf dan Sosio-Religi Pulau Tangnga Sulawesi Barat - Abu Muslim (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
This research concentrates on the actual religion surrounding the famed tomb-archeology of Sulawesi. This study, which focusses in particular on the Muslim religious leaders in Polewali Mandar, must first consider the first ancient tombs in Polman. In particular, we focus on the tomb at the Tangnga Island District of Binuang Polewali Mandar. Our selection of the tomb of Sheikh Bil Ma’ruf is motivated by that man’s key role and his remarkable persona given a society in which the veneration of tombs was central to people’s beliefs, and given that tomb archaeology can shed light on the sociology of a past society. It seems that the degree of veneration of a tomb corresponds to the honour in which a certain character’s memory is held. It seems that the veneration of Sheikh bil Ma’ruf’s tomb is directly proportional to the public celebration of this man’s deeds in his lifetime and the example that he gave to the flourishing local Islamic community in Sulawesi that came to be. Keywords: Sheikh Bil Ma’ruf, tomb,Sociology of Religy,Archeology Penelitian ini adalah studi tentang arkeologi-religi dengan makam sebagai objek kajiannya. Penelitian ini, menghendaki sebuah penelusuran arkeologis terhadap makam tokoh agama Islam di Polewali Mandar dengan terlebih dahulu melakukan inventarisasi makam-makam kuno di Polman. Objek kajian arkeologi religi dilakukan pada makam syekh Bil Ma’ruf di Pulau Tangnga Kecamatan Binuang Kabupaten Polewali Mandar. Pemilihan objek makam sangat ditentukan oleh peran tokoh tersebut semasa hidupnya yang mempunyai peran keagamaan serta ketokohan kuat di tengah-tengah masyarakat. analisis sosial dilakukan untuk melihat lakon masyarakat terhadap makam. Hal ini sebagai pengejewantahan dari Archeology is sociology for the past. Hasil penelitian menunjukkan bahwa peranan tokoh yang dimakamkan berbanding lurus dengan perilaku masyarakat terhadap makam dengan melakukan lakuan-lakuan bernuansa keagamaan yang terangkum dalam hajatan-hajatan yang dilakukannya serta pola keberislaman masyarakat setempat. Kata Kunci: Syekh Bil Ma’ruf, Makam, Sosiologi Religi, Arkeologi